Revised taxonomy and redescription of two species of the Peripatidae (Onychophora) from Brazil: a step towards consistent terminology of morphological characters - de Sena Oliveira, Ivo; Wieloch, Alfredo Hannemann; Mayer, Georg (Zootaxa, 2010)
Based on the supposed quadrangular shape of the basal pieces of dorsal primary papillae, several species of the “Caribbean group” of the neotropical Peripatidae, including Macroperipatus acacioi and M. machadoi, were assigned to Macroperipatus. So far, the quadrangular shape of dermal papillae was confirmed only for M. torquatus, the type species of the genus. Previous observations revealed that the putatively quadrangular shape reported from other species of the “Caribbean group” might be a fixation artefact. Hence, detailed reinvestigations of all putative Macroperipatus species are required to clarify their taxonomy. In the present study, two species of the “Caribbean group”, M. acacioi and M. machadoi, are analyzed and redescribed, based on type material and topotype specimens collected at the corresponding type localities. The original descriptions of both species are complemented with data obtained from scanning electron microscopy, in addition to conventional morphological methods. The quadrangular bases of primary papillae are shown to be absent from M. acacioi and M. machadoi, thus suggesting that these two species are not closely related to M. torquatus. The new data instead suggest that these two species are representatives of Epiperipatus: E. acacioi comb. nov. and E. machadoi comb. nov.. The present study highlights the use of scanning electron microscopy for clarifying the taxonomy and phylogeny of the neotropical Peripatidae. It also reveals gaps in taxon sampling and problems regarding the ambiguous terminology of morphological characters used for describing the anatomy of peripatids. An attempt is made towards a consistent terminology for species (re)descriptions and studies of onychophoran anatomy and phylogeny.